2020
DOI: 10.1038/s41598-020-71329-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in Parkinson’s disease astrocytes

Abstract: in parkinson`s disease (pD), the loss of dopaminergic (DA) neurons in the substantia nigra pars compacta is associated with Lewy bodies arising from the accumulation of alpha-synuclein protein which leads ultimately to movement impairment. While pD has been considered a disease of the DA neurons, a glial contribution, in particular that of astrocytes, in pD pathogenesis is starting to be uncovered. Here, we report findings from astrocytes derived from induced pluripotent stem cells of LRRK2 G2019S mutant patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 49 publications
4
101
0
Order By: Relevance
“…PD-variant-containing astrocytes display increased production of pro-inflammatory cytokines when exposed to aSYN monomers but not when exposed to aSYN fibrils or F110 A recent study suggested that PD astrocytes may show an exacerbated response to pro-inflammatory stressors (Sonninen et al, 2020). We therefore assessed pro-inflammatory cytokine release from astrocytes differentiated from iPSCs generated from PD patients with genetic variants in PARK2, LRRK2, SNCA, or GBA, as well as from patients with idiopathic PD (Figure 3A).…”
Section: Access Fraction (Figuresmentioning
confidence: 99%
“…PD-variant-containing astrocytes display increased production of pro-inflammatory cytokines when exposed to aSYN monomers but not when exposed to aSYN fibrils or F110 A recent study suggested that PD astrocytes may show an exacerbated response to pro-inflammatory stressors (Sonninen et al, 2020). We therefore assessed pro-inflammatory cytokine release from astrocytes differentiated from iPSCs generated from PD patients with genetic variants in PARK2, LRRK2, SNCA, or GBA, as well as from patients with idiopathic PD (Figure 3A).…”
Section: Access Fraction (Figuresmentioning
confidence: 99%
“…The secretion to the medium was increased for several polyamines, such as putrescine and spermidine and the levels of their precursors, arginine and ornithine, were elevated in astrocytes. Polyamines are important for various cellular processes, such as cell proliferation and differentiation, gene transcription and translation, as well as regulation of ion channel and receptor activity (119). Notably, changes in polyamine levels were also detected in the cerebrospinal fluid (CSF) of PD patients supporting the relevance of the data obtained in the iPSC models (124).…”
Section: Ipsc-derived Astrocyte Models To Study Metabolism In Neurodegenerative Diseasesmentioning
confidence: 54%
“…Our laboratory has demonstrated that PD astrocytes exhibit metabolic abnormalities, disturbed Ca 2+ homeostasis, impaired mitochondrial function, and an increased release of cytokines upon inflammatory stimulation 34 . Increased levels of polyamines and polyamine precursors and decreased levels of lysophosphatidylethanolamine reported in PD astrocytes 34 have also been observed in PD patients 36,37 . The activation of chaperone‐mediated autophagy reduced the toxic effects of PD astrocytes on cocultured neurons in one study (Table 1).…”
Section: Astrocytesmentioning
confidence: 91%
“…However, the studies on iPSC‐derived astrocytes carrying PD‐associated mutations LRRK2 G2019S and GBA1 N370S have suggested that PD astrocytes have impaired ability to degrade α‐synuclein 32‐34 and can induce α‐synuclein accumulation, neurite dystrophy, and cell death in cocultured neurons 35 . Our laboratory has demonstrated that PD astrocytes exhibit metabolic abnormalities, disturbed Ca 2+ homeostasis, impaired mitochondrial function, and an increased release of cytokines upon inflammatory stimulation 34 . Increased levels of polyamines and polyamine precursors and decreased levels of lysophosphatidylethanolamine reported in PD astrocytes 34 have also been observed in PD patients 36,37 .…”
Section: Astrocytesmentioning
confidence: 96%
See 1 more Smart Citation